2021
DOI: 10.1001/jamanetworkopen.2020.33967
|View full text |Cite
|
Sign up to set email alerts
|

Medical Oncology Professionals’ Perceptions of Telehealth Video Visits

Abstract: IMPORTANCETelehealth has emerged as a means of improving access and reducing cost for medical oncology care; however, use by specialists prior to the coronavirus disease 2019 (COVID-19) pandemic still remained low. Medical oncology professionals' perceptions of telehealth for cancer care are largely unknown, but are critical to telehealth utilization and expansion efforts. OBJECTIVE To identify medical oncology health professionals' perceptions of the barriers to and benefits of telehealth video visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 21 publications
9
115
0
3
Order By: Relevance
“…Similar to other studies, physicians favored office clinics because of the need to make comprehensive assessments including physical examinations [14,19]. In-office appointments allowed the physicians to do a full assessment, admit the patient if needed, and provide acute care.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to other studies, physicians favored office clinics because of the need to make comprehensive assessments including physical examinations [14,19]. In-office appointments allowed the physicians to do a full assessment, admit the patient if needed, and provide acute care.…”
Section: Discussionmentioning
confidence: 85%
“…In-office appointments allowed the physicians to do a full assessment, admit the patient if needed, and provide acute care. Heyer et al clarified that it was difficult to instruct the patients to do a physical examination, and physical examination that was done through telemedicine was limited to inspection most of the time [ 19 ]. Despite that, the vast majority of this study’s participants agreed that contacting patients using telemedicine was easy, and the information provided to the physician was clear, 61% of our participants believed that taking history using telemedicine was not easier than office clinics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cost savings, use of these alternative care pathways may improve cancer care access and quality, align more closely with patient preferences, and provide additional opportunities for patient engagement around their treatment [97,98]. Oncologists, for example, have noted telehealth's potential to provide more frequent follow-up, patient convenience and opportunities for patients to ask questions and engage family members in treatment conversations [99]. A recent survey of patients with breast and gynecological cancer using telehealth during the pandemic found high satisfaction rates, agreement that telehealth services activated them around their health, and beliefs that these services should be available in addition to in-person services [100].…”
Section: Digital Technology and Alternative Care Pathwaysmentioning
confidence: 99%
“…However, Heyer et al identified provider concerns about the ability to establish or maintain a provider-patient bond and deliver sensitive or complicated information through telehealth [99]. They also reported that copayments for a telehealth visit could hinder patient uptake because of patients' apprehension about paying for a video versus an in-person appointment.…”
Section: Digital Technology and Alternative Care Pathwaysmentioning
confidence: 99%
“…Prior to the pandemic, utilization of telehealth in cancer care was limited and variable, with notable barriers including access to technology and inconsistent reimbursement. 2 Significant strides have been made to expand telehealth services, both through improved access to technology and more consistent insurance reimbursement. 3,4 The pandemic has served as a realworld trial of implementation of telehealth services, and while success is not guaranteed, telehealth holds a clear advantage when considering expanded access to care, both in terms of geographic and social distance.…”
Section: Presentmentioning
confidence: 99%